Unveiling the Power of Race and Education in Shaping Entrepreneurial Dreams: An Empirical Study in Florida - Donovan Collier; Ravi Chinta (Administrative Sciences)
This study investigates the main effects and the interaction effects of race and education on entrepreneurial intentions in the pre-startup phase, using logistic regression analysis on a sample of 967 respondents from Florida. Blacks and Other Nonwhites are compared to Whites in the logistic regression analysis. As the largest empirical study of its kind at the state level in the U.S., it addresses a gap in the literature by focusing on a narrowly defined geographic area. The findings reveal significant differences in entrepreneurial intentions among racial groups, with education playing a crucial role. Policy implications include the need for tailored support programs and inclusive financial products to foster a more equitable entrepreneurial ecosystem. This study underscores the importance of entrepreneurial education and highlights the necessity for ongoing research to understand the unique challenges faced by Nonwhite entrepreneurs, ultimately contributing to a more inclusive and dynamic economy.